The International Migration System Between Turkey and Russia: Project-Tied Migrant Workers in Moscow - (:unkn) unknown (WILEY-BLACKWELL, 2012)
The last 50 years of emigration history in Turkey indicate that the migratory flows of Turkish citizens have consecutively become a part of various migratory systems. In this essay, our main aims are twofold. First, we attempt to document the dynamics and mechanism of project-tied migration from Turkey to the Russian Federation, focusing in particular on the case of project-tied workers migrating from Turkey to Moscow. Second, this effort intends to elaborate on the research on migratory systems between Turkey and the former communist countries of Eastern Europe and Central and Northern Asian countries, mainly referring to macro-, micro- and meso-level factors affecting the relevant migration systems. In this paper, in which we tackle the various migration systems with which Turkey is involved, we conclude by arguing that parallel to the new migration patterns that have been experienced throughout the post-Soviet geographies, the internalization process of Turkish constructors within the changing dynamics of Turkish foreign policy has widened the direction of the migration flows from Turkey by introducing new migrant worker profiles to different regions. In this sense, short-term labour migrants, shuttle traders and in particular project-tied migrant workers show not only the important role that migrants may play in the shift towards a market-based economy in the Russian Federation, but also how they have become crucial actors of the migration system between Turkey and Russia.